KAJIAN KADAR PROTEIN, SERAT, HCN, DAN SIFAT ORGANOLEPTIK PROL TAPE SINGKONG DENGAN SUBSTITUSI TAPE KULIT SINGKONG - Putri, Septi Wulan Adi; Hersoelistyorini, Wikanastri; Suyanto, Agus (Universitas Muhammadiyah Semarang, 2012)
This study aims to analysis the contents of protein, fiber, HCN, and the organoleptic propertiesof Cassava Tapae Cake with Substitution with Cassava Peel Tapae. The method used was experimentaland research design is completely randomized design (CRD) with varition of cassava peel tapae are 0,20%, 40%, 60%, 80%, and 100%. Results of protein analysis are 0.9608%, 1.2354%, 1.5099%,1.7844%, 1.9217%, and 2.1962%. fiber contents respectively it was 87.88%, 93.36%, 93.81%, 94.00%,94.90% and 94.93%. HCN content obtained negative results. The higher the substitution of cassavapeel tapae the higher the protein content and fiber content. Organoleptic properties mixed withcassava peel tapae that is taste a little bitter, compact texture, aroma is not sour and color tendency ofblack.